Exploring the Nexus of Nursing Competency Development: Insights from Input-Process-Output Dynamics in Education - Vera, Glenda P. De (International Journal of Research in Interdisciplinary Studies, 2024)
This study examines the nursing competency considering the input process-output involve in the academic setting. It explains how the output variable is impacted by the input and process variables. Utilizing the input variables of the study includes facilities and faculty. The curriculum design are process variables. The output variable is the core competencies expected from the nursing students. Important clinical competencies were considered: safe and quality nursing care, collaboration and teamwork, and ethico-legal responsibility. It has been established from this study that the General Systems Theory considering input-process-output explains how the variable affects the other. The study reveals that the input does not affect the output however the process variable affects the output. The outcome-based education significantly affects core competency. The use of an outcome-based education as the process and approach in the implementation of the curriculum helps in the attainment of nursing core competency. As the nursing program utilizes the competency approach, it highlights the learner performance and achievement of its outcome. It enables them to perform nursing skills competently thus aiding in positive patient health outcome.